Does ovarian sex cord tumour with annular tubules produce progesterone?. Issue 1 (January 1986) - Dolan, J; Al-Timimi, A H; Richards, S M; Jeffs, J B; Mason, G C; Smith, D B; Hasleton, P S
Abstract : Probable progesterone production was identified by an immunoperoxidase assay in a case of an ovarian sex cord tumour with annular tubules. The tumour was associated with a serous cystadenofibroma in the opposite ovary and with adenoma malignum (adenocarcinoma) of the cervix.